2004
DOI: 10.1238/physica.topical.109a00159
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties and Raman Scattering of Vanadium Ladder Compounds

Abstract: We investigate electronic and optical properties of the V-based ladder compounds NaV2O5, the iso-structural CaV2O5 as well as MgV2O5, which differs from NaV2O5 and CaV2O5 in the c axis stacking. We calculate ab initio the Ag phonon modes in these compounds as a basis for the investigation of the electron-phonon and spin-phonon coupling. The phonon modes together with the dielectric tensors as a function of the corresponding ion displacements are the starting point for the calculation of the Ag Raman scattering. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Due to the asymmetric crystal environment of the V ions in NaV 2 O 5 , the strongest lattice coupling is a Holstein-like electron-phonon interaction involving the d xy electrons. 20,24 We investigate the extended Hubbard model with Holstein coupling, introduced in Ref. 23, using high precision Density Matrix Renormalization Group (DMRG) calculations on isolated and on two coupled ladders.…”
Section: 17mentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the asymmetric crystal environment of the V ions in NaV 2 O 5 , the strongest lattice coupling is a Holstein-like electron-phonon interaction involving the d xy electrons. 20,24 We investigate the extended Hubbard model with Holstein coupling, introduced in Ref. 23, using high precision Density Matrix Renormalization Group (DMRG) calculations on isolated and on two coupled ladders.…”
Section: 17mentioning
confidence: 99%
“…1. The parameters are taken from LDA calculations 24 ; the hopping amplitudes t ij are compatible with earlier calculations. 25,39 The lattice parameters C and κ were extracted by comparing the total energy and the inter-ionic forces in distorted and undistorted lattices.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A zigzag charge order as observed in NaV 2 O 5 [4] is already created in this model by the nearestneighbor Coulomb repulsion V for an isolated ladder, but only at overly large values of V [5-10]. In a recent DensityMatrix Renormalization Group (DMRG) study [8], we showed that the inclusion of a strong effective Holstein coupling to the lattice, which was found in local-density approximation (LDA) calculations [11], reduces the required Coulomb repulsion to a realistic value. The DMRG calculations then yielded good agreement between theoretical and experimental results for the amount of charge order, the extent of lattice distortion in the c direction, the effective spin coupling J eff in the b direction, and the charge gap.…”
mentioning
confidence: 92%